We Go on a Subway - Mattern, Joanne, 1963- (Egremont, MA : Red Chair Press, 2020)
"What to expect from a trip on a subway"--Provided by publisher.
Includes index
Keywords: Transportation -- Juvenile literature; Subways -- Juvenile literature